Seismic Study of RCC Building With Regular and Irregular Plan Using NBC 105:2020 (International Journal of Innovative Research in Engineering & Management, 2022)
In building construction various regular  structures are provided. Irregular structures are also provided  during the construction. Due to earthquake various studies  should be made for these irregularities. For the minimization  of the damage of the structure due to earthquake necessary  precautions should be taken during the design phase. Various  damages may occur during construction due to seismic  excitations. Damage in the structure will not be same due to  various configuration, region, etc. The seismic behavior of  the structure depends upon structural system, soil location,  quality of the construction, earthquake characteristics and its  maintenance. In this paper 10 storey building is considered  for both regular and irregular structure. Model of the building is done in ETABS-2016. Loads that are considered such as  earthquake/ dead/ and live load in both axis for purpose of  analysis. Various types of load combinations are taken  according to NBC 105:2020. In this paper regular and  irregular plan of building are put under various seismic  conditions. The primary goal of the paper is to observe the  various performances between the models and which will  have a better performance between the two. In the present  study RCC building models having G+9 stories with regular  and irregular plan considered for analysis. The analysis of  model is done using dynamic method in ETABS software.  At last, the results of seismic behavior of buildings are  compared about the base drifts, shear, displacement, member  forces, overturning moment, time period, stiffness.
Keywords: Base shear; Storey Shear; Seismic Analysis; Storey Drift